THE INFLUENCES OF AVAILABLE SOIL WATER DEPLETION FRACTION TO GROWTHS AND YIELDS OF THREE SOYBEAN (Glycine Max (L) Merril) VARIETIES - Ardiyasa Komang (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The objective of this research was to find out the influences of available soil water depletion fraction to growthsand yields of three soybean varieties. This research used a factorial design in a completely randomized designwith the first factor was the available soilwater depletion fraction (p), which contained of three treatment levelsof (p); they were p1 (p=0.2 AW), p2 (p=0.4 AW), and p3 (p= 0.6 AW). The second factor was soybean varietiescontaining of three varieties; V1 = Willis, V2 = Kaba, and V3 = Tanggamus, which were repeated three times.Irrigationwas conducted when soil water levels was close to or above threshold of available soilwater depletionwhichwas determined bymeasuringwater level at gypsumblock and ohmmeter device. Irrigationwas conductedby returning water level to field capacity condition. Treatment of available soil water depletion fraction for theplants influences soybean in growth phase ofWilis (V1) variety, Kaba (V2) variety and Tanggamus (V3) variety.Observation data frominweek 8 of three showed that the highest stemgrowthwas in Kaba variety (55.87 cm) atp2 treatment (p=0.4 AW). The highest leave amountwas Kaba variety (66.93 leaves) at treatmentp2 (p=0.4 AW).The highest production was in Kaba variety (71.33gr) at treatment p2 (p=0.4 AW). The highest irrigationnecessitywas in treatment p2with 18mm water irrigation, and then followed by p3with 13.5mm and finally p1with 9mm. The lowirrigationwater necessity was influenced by high rainfall level of 578mmwith 32 rainy daysduring research.Keywords: soybeans,available soilwaterdepletion fraction, gypsumblock